International tax competition and coordination with a global minimum tax - Devereux, MP (University of Chicago Press, 2023)
This paper investigates the incentives for countries to implement and maintain the global minimum tax introduced by the G20/OECD’s Inclusive Framework 2021 agreement: Pillar 2. It argues that the agreement has sufficient elements to create incentives for large headquarters countries to implement it. Conditional on them doing so, there is an incentive for host countries to follow suit. The agreement would put a significant floor on tax competition. However, there are caveats to this argument in terms of complexity and the incentive to maintain some provisions that are likely to raise little revenue.